Restoration of lapsed beech pollards in the Basque region of Spain: comparison of different cutting techniques. Issue 3 (3rd July 2021) - Read, Helen; Bengtsson, Vikki; Castro, Alberto; Harris, Reg; Wheater, C. Philip
ABSTRACT: Methods used to restore lapsed beech pollards by pruning were compared across four sites in northern Spain. Tree response, between five and 10 years after cutting, was compared with information about the cutting techniques used. The results provide further information about the techniques that maximise the success of working trees with this history of management in the Basque region of Spain, and furthers our understanding of managing these types of trees wherever they occur. When restoring lapsed pollards, choose trees in moderate shade with many branches. Retain at least three uncut branches spread around the tree, avoid cutting too close to the bolling and leave some foliage. If possible, cut branches less than 30 cm in diameter and with good epicormic growth. Cutting close to the bolling brings greater risks. A flow chart is provided to help the decision process.